2022
DOI: 10.1002/aenm.202103128
|View full text |Cite
|
Sign up to set email alerts
|

Perovskite Solar Cells with Carbon‐Based Electrodes – Quantification of Losses and Strategies to Overcome Them

Abstract: Carbon‐based electrodes represent a promising approach to improve stability and up‐scalability of perovskite photovoltaics. The temperature at which these contacts are processed defines the absorber grain size of the perovskite solar cell: in cells with low‐temperature carbon‐based electrodes (L‐CPSCs), layer‐by‐layer deposition is possible, allowing perovskite crystals to be large (>100 nm), while in cells with high‐temperature carbon‐based contacts (H‐CPSCs), crystals are constrained to 10–20 nm in size. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 76 publications
(92 reference statements)
0
35
0
Order By: Relevance
“…Figure illustrates both low‐ and high‐temperature processible carbon‐electrode‐based PSCs with/without a HSL. [ 218 ]…”
Section: High‐ and Low‐temperature‐processible C‐pscs: The Path Towar...mentioning
confidence: 99%
“…Figure illustrates both low‐ and high‐temperature processible carbon‐electrode‐based PSCs with/without a HSL. [ 218 ]…”
Section: High‐ and Low‐temperature‐processible C‐pscs: The Path Towar...mentioning
confidence: 99%
“…Thus, HP RS memories should explore these alternatives such as carbonaceous electrodes (graphene, carbon), which have been recently established in HP photovoltaics as they offer cheaper solutions in reducing electrode costs. [126][127][128] 3. When employing the selected design structure, how does the choice of electrode material affect RS characteristics?…”
Section: Electrode Selection Strategies For Hp Rs Devicesmentioning
confidence: 99%
“…Thus, HP RS memories should explore these alternatives such as carbonaceous electrodes (graphene, carbon), which have been recently established in HP photovoltaics as they offer cheaper solutions in reducing electrode costs. 126–128…”
Section: Electrode Selection Strategies For Hp Rs Devicesmentioning
confidence: 99%
“…116 Recent work demonstrated that the major limiting factor for carbon-based counter electrodes in perovskite solar cells is the severe performance losses at the counter electrode interfaces. 117 Kim and coworkers developed a two dimensional perovskite electron blocking layer in hole-conductor free devices in order to reduce the charge losses at interfaces, which enables a promising PCE of 18.5%. 118…”
Section: Carbonmentioning
confidence: 99%